Defense-Related Enzyme Activities and Metabolomic Analysis Reveal Differentially Accumulated Metabolites and Response Pathways for Sheath Blight Resistance in Rice - Xiurong Yang; Shuangyong Yan; Yuejiao Li; Guangsheng Li; Yujiao Zhao; Shuqin Sun; Jingping Su; Zhongqiu Cui; Jianfei Huo; Yue Sun; Heng Yi; Zhibin Li; et al. (Plants)
Rice sheath blight (RSB), caused by the pathogenic fungus Rhizoctonia solani, poses a significant threat to global food security. The defense mechanisms employed by rice against RSB are not well understood. In our study, we analyzed the interactions between rice and R. solani by comparing the phenotypic changes, ROS content, and metabolite variations in both tolerant and susceptible rice varieties during the early stages of fungal infection. Notably, there were distinct phenotypic differences in the response to R. solani between the tolerant cultivar Zhengdao22 (ZD) and the susceptible cultivar Xinzhi No.1 (XZ). We observed that the activities of five defense-related enzymes in both tolerant and susceptible cultivars changed dynamically from 0 to 72 h post-infection with R. solani. In particular, the activities of superoxide dismutase and peroxidase were closely associated with resistance to RSB. Metabolomic analysis revealed 825 differentially accumulated metabolites (DAMs) between the tolerant and susceptible varieties, with 493 DAMs responding to R. solani infection. Among these, lipids and lipid-like molecules, organic oxygen compounds, phenylpropanoids and polyketides, organoheterocyclic compounds, and organic acids and their derivatives were the most significantly enriched. One DAM, P-coumaraldehyde, which responded to R. solani infection, was found to effectively inhibit the growth of R. solani, Magnaporthe grisea, and Ustilaginoidea virens. Additionally, multiple metabolic pathways, including amino acid metabolism, carbohydrate metabolism, metabolism of cofactors and vitamins, and metabolism of terpenoids and polyketides, are likely involved in RSB resistance. Our research provides valuable insights into the molecular mechanisms underlying the interaction between rice and R. solani.